(3GdJShjb GdGdcJQhfj (B/s - (3CMeO, eMeO SejQs ((3YeGf(B: s (3OGQ GdeSjQI(B, s, 2008)
(3eONd Gdi GdCYeGd GdEdcJQhfjI(B- (3fXGe GdeYdheGJ GdJShjbjI ddCYeGd GdEdcJQhfjI(B- (3EOGQI GdJejjR ceONd dehGLgI GdefGaSI(B- (3eONd Gdi YUQ GdNOeI GdEdcJQhfjI(B- (3GdJShjb GdEdcJQhfj(B- (3GdJNWjW GdESJQGJjLj ddJShjb GdEdcJQhfj(B- (3GdEfJQfJ hJShjb GdNOeGJ YHQ GdCfJQfJ(B- (3JSYjQ GdefJLGJ GdeHGYI YHQ GdEfJQfJ(B- (3GdEYdGf YHQ GdCfJQfJ(B- (3GdJhRjY aj YUQ GdEfJQfJ(B- (3GdeLJeYGJ GdEaJQGVjI(B- (3GdNUhUjI hCef GdeYdheGJs
(3GdeQGLY U(B.303s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdJShjb(B- (3GdCfJQfJs; (3JcfhdhLjG GdeYdheGJs